The Relativity in the Absolute Authority of the Central Government in Religious Affairs - Fatchan Gani Wardhana, Allan; Addi Fauzani, Muhammad; Riza Hakiki, Yuniar (KnE Social Sciences, 2023)
The legal policy of the regional government, post-political reform, puts religious affairs under the absolute administrative authority of the central government. However, the development of society requires religious affairs to also be taken care of by the regional government. We argued that there is relativity in the absolute administrative affairs of the central government authority in the scope of religion. This research aimed to analyze and identify the form of relativity in the absolute administration of the central government in religious affairs. Second, the advantages and disadvantages of the absence of certainty related to the absolute administration of the central government in religious affairs were discussed. The method used in the study was legal doctrinal research with statutory and conceptual approaches. The results of the study concluded that the implementation of absolute government administration in the field of religion turned out to be relative, with the involvement of the regional government in managing and regulating religious affairs. This occurs in the affairs of Islamic boarding schools, hajj and umrah, zakat, and the maintenance of religious harmony. Second, there are advantages and disadvantages to the involvement of regional governments in carrying out religious affairs. Among the advantages, namely the financial burden and the activities of the central government in the administration of religious affairs can be assisted by the regional government budget. The weakness was in the regulation and implementation of the absolute government administration in religious affairs by regional governments due to a lack of understanding of the development of government affairs. Keywords: Relativity, Government Administration, Central Government, Religion